Hubungan Hidup Bersih dan Sehat dengan Tingkat Kebugaran Jasmani Siswa Kelas X di SMAN 2 Lamongan - Wahana, Satya (Journal of Sport Science and Education, 2018)
Clean and healthy life behavior is all health behavior that is done on the awareness so that family or family members can help themselves in the health sector and play an active role in health activities in the community. Physical fitness is the ability of a person to perform daily hard activity easily without feeling tired, and still have residual or reserve energy to enjoy leisure or another purposes that can be used at any time. The purpose of this research is to understanding about relationship between clean and healthy living behavior with a level physical fitness of X class students in State Senior High School 2 Lamongan.This research is descriptive research with quantitative method. The population in this research is the students of class X in State Senior High School 2 Lamongan. Sampling is non probability with total sample of 205 students from 445 students. Data analysis used in this study using statistical analysis. The results of this study can be known data of healthy and healthy living behavior of normal distribution as well as data of physical fitness which also distributed normally. The relationship between clean and healthy life behavior with physical fitness level of grade X students at State Senior High School 2 Lamongan has significant relationship and has enough correlation criteria. The result of hypothesis in this research is there is relationship of clean and healthy life behavior with level of physical fitness of class X student at State Senior High School 2 Lamongan.